Growth and Yield of Soybean (Glycine max L.) as Influenced by Phosphorus (Bangladesh Journal of Scientific and Industrial Research, 2008)
The experiment was conducted to find out the influence of phosphorus (P) on growth and yield of soybean (Glycine max L., variety: G-2). The treatments were: control (P1) and with the application of 50% (P2), 75 % (P3), 100 % (P4), 125 % (P5) and 150 % (P6) of the BARC recommended dose of P. Nitrogen, K and S were applied as blanket as per BARC recommendation. Seeds were inoculated with Bradyrhizobium inoculum before sowing. All the treatments of P application showed higher growth than that of the control. P5 treatment (11.25 kg P ha-1) showed maximum growth and yield, which was 84.73% higher than that of control. The yield changed as a parabola curve with the increase of P application. The yield component, namely number of pods plant-1, number of seeds pod-1, pod weight plant-1 and number of seed plant-1 increased with the increase of P levels up to 11.25 kg P ha-1. The application of P at 11.25 kg ha-1 (25% higher over BARC recommendation) produced the highest seed yield of soybean (7.50 g plant-1). So, for better yield of soybean in silty clay loam soil of Jahangirnagar University farm, application of P should be increased 25 % higher over BARC recommendation.Key words: Soybean, Phosphorus, Growth, YieldDOI = 10.3329/bjsir.v43i3.1151Bangladesh J. Sci. Ind. Res. 43(3), 359-368, 2008